Carbon fibers supported NiSe nanowire arrays as efficient and flexible electrocatalysts for the oxygen evolution reaction. (April 2018) - Han, Xiuxiu; Tong, Xili; Wu, Gangpin; Yang, Nianjun; Guo, Xiang-Yun
Abstract: The development of flexible, efficient, and earth-abundant electrocatalysts on carbon substrates for oxygen evolution reaction (OER) is of great significance for flexible power sources. Herein, NiSe nanowire arrays are controllably grown on carbon fibers (CFs) by a simple solvothermal process. The NiSe/CFs catalyst was characterized with electron microscopy, X-ray photoelectron spectroscopy, and X-ray diffraction techniques. In 1.0 M KOH, the performance of the NiSe/CFs catalyst towards electrocatalytic OER was investigated. At the current density of 50 and 100 mA cm −2, the overpotentials are only 318 and 334 mV, respectively. The Tafel slope is 46 mV dec −1 . Moreover, the NiSe/CFs catalyst shows no degradation after more than 120 h of continuous oxygen evolution. The performance is thus superior to the commercial IrO2 catalysts. The excellent activity of the NiSe/CFs catalyst for OER benefits from its structural merits and the in situ formed catalytically active species. This work sheds light on designing highly efficient, stable, and cheap catalysts for flexible OER catalysts. Graphical abstract: Image 1